Auxetic materials for sports applications - Sanami, M.; Ravirala, N.; Alderson, K.; Alderson, A. (Procedia Engineering, 2014)
In this paper, the auxetic effect is introduced, the range of auxetic materials is briefly reviewed, and research demonstrating benefits having potential in sports applications is highlighted. These include the use of auxetic materials in impact protector devices (pads, gloves, helmets and mats) exploiting better conformability for comfort and support, and enhanced energy absorption for lighter and/or thinner components. FE simulations are reported for a new type of auxetic honeycomb having potential in helmet applications, along with indentation testing of auxetic and non-auxetic foams for assessment in protective pads and running shoes applications, for example.